2011
DOI: 10.1038/nsmb.2144
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of tRNA agmatinylation essential for AUA codon decoding

Abstract: The cytidine at the first position of the anticodon (C34) in the AUA codon-specific archaeal tRNA(Ile2) is modified to 2-agmatinylcytidine (agm(2)C or agmatidine), an agmatine-conjugated cytidine derivative, which is crucial for the precise decoding of the genetic code. Agm(2)C is synthesized by tRNA(Ile)-agm(2)C synthetase (TiaS) in an ATP-dependent manner. Here we present the crystal structures of the Archaeoglobus fulgidus TiaS-tRNA(Ile2) complexed with ATP, or with AMPCPP and agmatine, revealing a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…A mutation study demonstrated the importance of U36 and A37. 30 Furthermore, A38 and C39 of tRNA Ile2 are expelled from the anticodon arm and located at the OBD. This interaction allows A38 located onto a concave hydrophobic surface of the OBD.…”
Section: Ile2mentioning
confidence: 99%
See 4 more Smart Citations
“…A mutation study demonstrated the importance of U36 and A37. 30 Furthermore, A38 and C39 of tRNA Ile2 are expelled from the anticodon arm and located at the OBD. This interaction allows A38 located onto a concave hydrophobic surface of the OBD.…”
Section: Ile2mentioning
confidence: 99%
“…4D). 30 Arg369 is a critical residue for agm 2 C formation. In addition, the replacement of either the G1-C72 or G2-C71 base pair of tRNA Ile2 with those of tRNA Met nearly eliminates the agmatine-accepting activity.…”
Section: Role Of Acceptor-stem Recognition By Tils and Tiasmentioning
confidence: 99%
See 3 more Smart Citations